Analisis Nilai Tambah dan Strategi Pengembangan Industri Olahan Kulit Buah Naga di Kabupaten Banyuwangi, Jawa Timur - Ahmad Haris Hasanuddin Slamet; Dini Nafisatul Mutmainah; Rafly Rizqullah; Fanecia Apriani (LPPM Universitas Terbuka, 2022)
Dragon fruit is one of the leading commodities in Banyuwangi Regency. In 2020, the dragon fruit commodity was recorded to have a land area of 4,787 Ha with a productivity of 263 Kw/Ha. High production causes the consumption of dragon fruit in the community is very high and results in the accumulation of dragon fruit skin. One alternative to overcome the buildup of dragon fruit skin is to use it into a product that is worth selling more. This study uses the value added analysis method and SWOT analysis to obtain the formulation of a strategy for developing the dragon fruit peel processing industry followed by a grand strategy and value added analysis using the hayami method. Meanwhile, based on the SWOT analysis of the IFE matrix value, a total value of 2,68 was obtained, the EFE matrix obtained a total value of 3,00. This value shows the potential for the development of the dragon fruit peel industry is in a strong position. Referring to the added value and SWOT analysis, it shows that the processing of dragon fruit peel waste into various processed products has the potential to be developed into an industry.